Am I there yet? The views of people with learning disability on forensic community rehabilitation. (14th December 2015) - Davis, Alana; Doyle, Michael; Quayle, Ethel; O'Rourke, Suzanne
Abstract : Purpose: – Previously, diversion from the criminal justice system for people with learning disability (LD) and serious forensic needs in Scotland meant hospitalisation. More recently new legislation has meant that community-based rehabilitation is possible for this group. The purpose of this paper is to qualitatively explore the views of people with LD subject to these legal orders. This is both a chance to work in partnership to improve services and also to make the voices of this potentially vulnerable group heard. Design/methodology/approach: – Semi-structured interviews were conducted with ten participants subject to a community-based order. All participants were male. Ages, index behaviour, and time spent on order varied. The data was transcribed and analysed using interpretative phenomenological analysis. Findings: – The main themes which emerged from the data were a taste of freedom, not being in control, getting control back, loneliness, and feeling like a service user. Participants described positives about community-based rehabilitation but also a number of negatives. Practical implications: – Participant accounts suggest that the current community rehabilitation model has some shortcomings which need to be addressed. Suggestions are made for improvements to the current model relating to: achieving clarity over the role of support staff and pathways out of the system; increasing opportunities for service users to voice concerns; empowering staff teams via extensive training and supervision; and directly addressing internalised stigma to promote community integration. Originality/value: – This is the first piece of work evaluating compulsory community forensic care for people with LD from the perspective of service users. It highlights difficulties with the system which could lead to helpful ways to evolve this model.